Intersectionality and Inclusion in Higher Education: Considerations about Universidad Nacional de Colombia - María Lucía Rivera Sanín (Universidad Pedagógica Nacional, 2016)
The project for the Measurement of Inclusion and Social Equality in Superior Education Institutions in Latin America (Miseal for its name in Spanish) evaluates social inclusion through six markers, making it necessary to understand and characterize the notion of intersectionality. This result of research paper presents two issues: in the first place, a review of the measurement obtained by contrasting two ways of understanding identity and their implications for interpreting it; in the second place, a reflection on the structure and the scope of the agreements ruling the Special Admission Program (paes) and the Admission and Academic Mobility Special Program (peama) given the figures of admission and permanence.